A crustacean lobula plate: Morphology, connections, and retinotopic organization - Bengochea, Mercedes (2018)
The lobula plate is part of the lobula complex, the third optic neuropil, in the optic lobes of insects. It has been extensively studied in dipterous insects, where its role in processing flow-field motion information used for controlling optomotor responses was discovered early. Recently, a lobula plate was also found in malacostracan crustaceans. Here, we provide the first detailed description of the neuroarchitecture, the input and output connections and the retinotopic organization of the lobula plate in a crustacean, the crab Neohelice granulata using a variety of histological methods that include silver reduced staining and mass staining with dextran-conjugated dyes. The lobula plate of this crab is a small elongated neuropil. It receives separated retinotopic inputs from columnar neurons of the medulla and the lobula. In the anteroposterior plane, the neuropil possesses four layers defined by the arborizations of such columnar inputs. Medulla projecting neurons arborize mainly in two of these layers, one on each side, while input neurons arriving from the lobula branch only in one. The neuropil contains at least two classes of tangential elements, one connecting with the lateral protocerebrum and the other that exits the optic lobes toward the supraesophageal ganglion. The number of layers in the crab's lobula plate, the retinotopic connections received from the medulla and from the lobula, and the presence of large tangential neurons exiting the neuropil, reflect the general structure of the insect lobula plate and, hence, provide support to the notion of an evolutionary conserved function for this neuropil.